Information Literacy Skills and the Use of Library Resources among Students in India - Mondal, Debdas (Academia Journal of Humanities & Social Sciences, 2026)
This study investigates the relationship between information literacy (IL) skills and library resource usage among students in public secondary schools in Paschim Bardhaman District, West Bengal, India. Using a descriptive survey method, data were collected from 400 students across grades 9 and 10 through a structured questionnaire. Findings reveal that the majority of students possess moderate IL skills, with notable weaknesses in evaluating sources and ethical information use. Textbooks were the most frequently used library resources, while digital tools were underutilised due to limited access to ICT and a lack of awareness. A strong positive correlation (r = 0.63, p < .01) and significant regression result (β = 0.63, p < .001) indicate that students with higher IL skills engage more frequently with library resources. The study highlights the urgent need for improved digital infrastructure, professional development for school librarians, and integration of IL instruction into classroom teaching to enhance students’ academic performance and lifelong learning capabilities.